1972
DOI: 10.1149/1.2404357
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of Carbon Electrodes in Aqueous and Nonaqueous Systems

Abstract: Cyclic voltammetry was used to investigate the surface phenomena and general electrochemical behavior encountered when glassy carbon and pyrolytic graphite are used as indicator electrodes in aqueous and nonaqueous (acetic acid, acetonitrile, dimethylformamide, and pyridine) media for inorganic (ferrocyanide and ferrocene) and organic (quinone) compounds. Factors evaluated included effects of method of preparation of the graphite, different resurfacing methods including magnitude of the induced electrostatic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0
3

Year Published

1972
1972
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(33 citation statements)
references
References 13 publications
3
27
0
3
Order By: Relevance
“…The k8 app values for diamond and glassy carbon reported herein are 5 ± 10 times larger than some values reported in the literature. Panzer and Elving reported similar values for DE p at 0.1 V/s in 0.1 M LiClO 4 /CH 3 CN on glassy carbon [11]. The k8 app values reported for platinum are generally 2 ± 4 times larger than those observed for carbon electrodes.…”
Section: Resultsmentioning
confidence: 67%
“…The k8 app values for diamond and glassy carbon reported herein are 5 ± 10 times larger than some values reported in the literature. Panzer and Elving reported similar values for DE p at 0.1 V/s in 0.1 M LiClO 4 /CH 3 CN on glassy carbon [11]. The k8 app values reported for platinum are generally 2 ± 4 times larger than those observed for carbon electrodes.…”
Section: Resultsmentioning
confidence: 67%
“…Scan rates were varied from 20 to 400 mV s −1 . The BAS reference electrode was calibrated using the [Fe(CN) 6 ] 3− /[Fe(CN) 6 ] 4− couple, [16] at ionic strengths relevant to the present work (see below). Based on these data, reduction potentials, E 1/2 are reported relative to the normal hydrogen electrode (NHE) by addition of 250 mV to observed BAS electrode values.…”
Section: Electrochemistrymentioning
confidence: 99%
“…This value is close to the value, 2.55 × 10 −7 cm 2 s −1 , reported for the same redox system in (EMIM)(NTf 2 ). 26 The more viscous medium not only lowers the diffusion coefficient but it also reduces the electron-transfer kinetics. Tachikawa et al have shown that a linear relationship exists between the heterogeneous electron-transfer rate constant and η −1 .…”
Section: Resultsmentioning
confidence: 99%